Comparative analysis of the efficacy of early and late surgical intervention for acute spinal cord injury: A systematic review and meta-analysis based on 16 studies. (October 2021) - Qiu, Yuanyuan; Chen, Yaping; Xie, Ying; Xie, Hongzhi; Dong, Jige
Abstract: Background: Spinal cord injuries (SCI) are a devastating condition and can lead to severe functional and psychosocial problems. However, the influence of the timing of the surgical intervention for acute SCI remains debated, with substantial variability in clinical practice. Thus, this study aims to compare the efficacy of early and late surgical intervention for acute SCI. Methods: A systematic search of PubMed, Embase, Cochrane Library and Web of Science up to January 10, 2021 was conducted for relevant studies that compared early and late acute SCI. Neurological outcomes were assessed by American Spinal Injury Association (ASIA). Early surgery was defined as the surgical intervention within 24 h after spinal injury. The primary outcome was the change of ASIA score from baseline to follow-up time after spinal injury. Second primary outcomes were clinical outcomes including neurological improvement rate, mortality, length of stay (LOS), charges ($), complications and ASIA Impairment Scale (AIS). All statistical analyses were performed using standard statistical procedures provided in Review Manager 5.2. Results: A total of 16 studies including 3977 SCI patients were identified finally. Our pooled results indicated that, compared with late surgery, patients who underwent early surgery experienced more ASIA score improvement, with pooled MDs of 2.32 points (95% CI 1.07–3.57; P  = 0.0003) in total motor scores, 5.13 points (95% CI 3.94–6.32; P  < 0.0001) in light touch scores, and 4.49 points (95% CI 2.22–6.76; P  = 0.0001) in pin prick scores respectively. In addition, patients receiving early surgery experienced more total motor score after surgery (MD 3.30; 95% CI 0.82–5.79; P  = 0.009). Patients who had early surgery also had higher neurological improvement rate (OR 1.66; 95% CI 1.19–2.31; P  = 0.003), shorter LOS (MD -4.77; 95% CI -7.42 to −2.12), less charges ($) (MD -0.33; 95% CI -0.43 to −0.22), lower incidence of complications (OR 0.62; 95% CI 0.48–0.81), and higher AIS improvement rate (OR 1.71; 95% CI 1.20–2.44) respectively. Conclusions: Compared with late surgery, acute SCI patients who underwent early surgery experienced greater recovery after spinal injury, with better neurological improvement, shorter LOS, less charges and lower incidence of complications. Highlights: ● Patients who underwent early surgery experienced more ASIA score improvement than late surgery. ● Patients who had early surgery also had higher neurological improvement rate. ● Acute SCI patients who underwent early surgery experienced greater recovery after spinal injury. ● Shorter LOS, less charges and lower incidence of complications was also observed in early surgery patients.